A rat model for studying effects of sacral neuromodulation on the contractile activity of a chronically inflamed bladder - Riazimand, Seyed-Hossein; Mense, Siegfried (BJU international, 2004)
OBJECTIVE: To develop an animal model in which the effects of electrical stimulation of the sacral nerves (sacral neuromodulation) on a chronic hyperactive urinary bladder can be studied. MATERIALS AND METHODS: In female rats the urinary bladder was instilled with mustard oil (0.4%); after 10 days the animals were anaesthetized with intraperitoneal urethane, the bladder catheterized and connected to a pressure transducer. Stimulating electrodes were placed into the sacral foramina bilaterally. The intensity and duration of sacral electrical stimulation was varied systematically to determine the effects of the sacral neuromodulation on bladder contractions. RESULTS: The main effect of the neuromodulation was an increase in the interval between contractions, i.e. during and for some time after the stimulation the contractions were completely abolished. The duration of the pause increased with the intensity and duration of stimulation. After the contractions had reappeared the frequency of contractions was reduced for a long period. In animals with chronic cystitis the effects of neuromodulation tended to be stronger (the pauses were longer) than in control animals with an intact bladder, but only in one test (increase of pause length with stimulus duration) was the difference statistically significant. CONCLUSIONS: The results show that this animal model is suitable for studying the effects and mechanisms of sacral neuromodulation on a chronic hyperactive urinary bladder.